Changing perspectives on marijuana use during early adolescence and young adulthood: Evidence from a panel of cross-sectional surveys. (1st December 2016) - Salas-Wright, Christopher P.; Vaughn, Michael G.; Perron, Brian E.; Gonzalez, Jennifer M. Reingle; Goings, Trenette Clark
Highlights: We examine marijuana-related differences across adolescence and young adulthood. Significant differences found between youth born in late-1980s and mid-1990s. The link between marijuana disapproval and use found to be invariant. Abstract: Introduction: Prior research has often overlooked potential cohort differences in marijuana views and use across adolescence and young adulthood. To begin to address this gap, we conduct an exploratory examination of marijuana views and use among American youth using a panel of cross-sectional surveys. Method: Findings are based on repeated, cross-sectional data collected annually from adolescents (ages 12–17; n = 230, 452) and young adults (ages 18–21; n = 120, 588) surveyed as part of the National Survey on Drug Use and Health between 2002 and 2014. For each of the birth years between 1986 and 1996, we combined a series of nationally representative cross-sections to provide multi-year data strings designed to approximate nationally representative cohorts. Results: Compared to youth born in the mid-to-late 1980s, youth born in the mid-1990s reported significantly higher levels of marijuana disapproval during the early adolescent years (Age 14: 1988 = 64.7%, 1994 = 70.4%) but lower levels of disapproval during the young adult years (Age 19: 1988 = 32.0%, 1994 = 25.0%; Age 20: 1988 = 27.9%, 1994 = 19.7%). Moreover, the prevalence of marijuana use among youth born in 1994 was significantly lower—compared to youth born in 1988—at age 14 (1988: 11.39%, 1994: 8.19%) and significantly higher at age 18 (1988: 29.67%, 1994: 34.83%). This pattern held even when adjusting for potential confounding by demographic changes in the population across the study period. Conclusions: We see evidence of changes in the perceptions of marijuana use among youth born during the late twentieth century.